Professional Identity as Gateway to Critical Practices: Identity Negotiations of Public Librarians in New Zealand with Implications for LIS Education and Practice. Issue 3 (2nd July 2020) - Pierson, Cameron M.; Goulding, Anne; Campbell-Meier, Jennifer
ABSTRACT: Librarian professional identity can be understood as a developmental process occurring over time and is indicative of a renegotiation of identity through experiences. This process transpires with or without cognitive grappling of identity and its influence on behaviour, making the renegotiation process either explicit or implicit. Among these experiences, education is a key developmental phase in which entrants begin to define conceptualisations of the profession and their identity within it. Critical, reflective, and reflexive practices can be understood as forms of identity negotiations relating to the practice of a profession in society. Effecting change within a profession through these practices requires first an examination of professional identity to understand the influences upon it. This paper reports on selected findings from interviews with practicing public librarians in New Zealand. It introduces the umbrella term critical practices for critical, reflective, and reflexive practice, defined as identity negotiations within the context introduced by this paper. In order to better effect critical practices, results suggest provision of cognitive spaces in educational settings can encourage explicit grappling with professional identity. Such spaces could encourage self-awareness of the identity process for entrants and begin the explicit recognition of the relationship between identity, behaviour, and practice.